The legal foundations and specifics of exercising corporate rights by individuals authorized to perform local self-government - Pyvovar, Inna; Tsikalo, Volodymyr; Lavryk, Nataliia; Bliakharskyi, Yaroslav; Slobozhan, Oleksandr (Edelweiss Applied Science and Technology, 2024)
Financial liberalization is a widely adopted policy for countries to enhance growth. Financial liberalization enables financial institutions to proceed with innovative activities by familiarizing themselves with fewer mortgage loans in the financial market. Financial liberalization is a widely adopted policy for countries to enhance growth; however, it is a complex and controversial issue, with different studies providing contrasting perspectives. Financial liberalization is considered an efficient way to measure and change the financial market and structure in order to reach a position to get financial liberalized markets under an efficient and effective guideline. In the case of Vietnam, very few scholars have investigated the issue of financial liberalization-led growth. This endeavor examines the effects of financial liberalization on economic growth in the presence of control variables for Vietnam over the period of 1990 to 2021. This study uses the Autoregressive Distributive Lag Model approach due to its several advantages. The results show that financial liberalization enhances economic growth, which implies that more liberalization results in enhanced growth in Vietnam. Improved access to credit is another positive outcome of financial liberalization, as it can result in greater access to credit for individuals and businesses, enabling them to make investments and expand their operations. Hence, the results support the neo-liberal view of liberalization.